Annual Plan, 1995-96 Vol. I Government of Orissa - Planning Commission (Planning Commission, 1995)
According to 1991 census the state had a total population of 316.60 lakh with the male and female population constituting 50.74% and 49.26% respectively accounting for 3.74% of the total population of the country. The density of population of the state at 203 is much lower than the national average of 273 per Sq.Km. An important silver lining on the horizon is that the decadal rate of growth of population during 1981-91 at 20.06% shows a marginal decline as compared to the rate of growth in the previous decade (1971-81) at 22.17%. Yet another silver lining is that the sex ratio of the state at 971 in 1991 is much higher than that of the country (929) as also higher than most of lie states in the North even though the sex ratio in the state itself has declined from 951 in 1981 to 1971 in 1991. With 86.2% of the population of the state living in rural area; lie state is predominantly rural. The increase in the extent of urbanisation in 1981-91 decade is 36.16 though rural urban migration both within and outside the state is an important phenomenon which is progressively on the increase.
Annual Plan, 1995-96 Orissa Vol. I
Government of Orissa